An evaluative study on the role of the Philippine Library Materials Project Foundation, Inc. in the collection development of selected academic libraries - Samson, Ma. Cristina B. (Institute of Library Science, University of the Philippines Diliman, 1995)
This study was conducted to examine and evaluate the impact of the Philippine Library Materials Project Foundation, Inc. (PLMP) in forty-five academic libraries with regards to their collection development programs. PLMP is a cooperative non-profit organization which collects materials abroad to help expand the resources of Philippine libraries.